Altered Chromogranin A Circulating Levels in Meniere's Disease. (23rd April 2015) - Teggi, Roberto; Colombo, Barbara; Trimarchi, Matteo; Bianco, Mimma; Manfredi, Angelo; Bussi, Mario; Corti, Angelo
Abstract : Objectives . Meniere's disease (MD) is an inner ear disorder characterized by episodic vertigo, ear fullness, and hearing loss; usually vertigo attacks cluster in specific period. We studied in MD patients the circulating levels of chromogranin A (CgA) and vasostatin-1 (VS-1), secreted by the neuroendocrine system and involved in the regulation of the endothelial barrier function. Methods . Serum levels were assessed in 37 MD patients and 36 controls. The ratio between VS-1 and CgA was calculated. Results . CgA was increased in patients compared to controls (1.46 versus 0.67 nM, p = 0.01 ) while no difference was detected for VS-1 (0.41 versus 0.39, resp.). CgA levels in patients positively correlated with the frequency of vertigo spells in the previous four weeks (p = 0.008 ) and negatively with the time in days from the last vertigo attack (p = 0.018 ). Furthermore, the VS-1/CgA ratio negatively correlated with the frequency of vertigo spells (p = 0.029 ) and positively correlated with the time from the last attack (p = 0.003 ). Conclusion . The results indicate that variations of CgA levels, but not of VS-1, occur in the blood of patients with active MD, depending on the frequency of vertigo spells and the time from the last crisis.